Breast cancer insights from Northern Israel: a comprehensive analysis of survival rates among Jewish and Arab women - Badran, Omar; Campisi-Pinto, Salvatore; Amna, Mahmoud Abu; Turgeman, Ilit; Yosef, Samih; Bar-Sela, Gil (Frontiers in Oncology, 2024)
This study investigates breast cancer survival rates between 2000 and 2022 in northern Israel, focusing on ethnicity, socioeconomic status, age at diagnosis, and the Charlson Comorbidity Index.Analyzing data from Clalit Health Services, we studied 8,431 breast cancer patients (6,395 Jewish, 2,036 Arab). We compared five-and ten-year survival rates across different demographics.Ethnicity showed a minor impact on survival (OR 1.12, 95% CI: 0.93 -1.35).Socioeconomic status had a significant effect, with a higher level of improving survival (OR 2.50, 95% CI: 2.04 -3.08). Age was crucial; women 18-39 had better survival than 60-100, but no significant difference was found between the 18-39 and 40-59 age groups (OR [CI 0.90 -1.53, p = 0.231]). For the Charlson Comorbidity Index, women with scores of 3-10 showed lower survival compared to scores of 0 and 1-2. There was a notable improvement in five-year survival rates among patients aged 18-59 diagnosed from 2009-2018 (90.7%) compared to 2000-2008 (86.9%) (p = 0.0046), but not in patients aged 60-100.The study highlights that socioeconomic status, age, and comorbidity scores are significant in determining survival rates for breast cancer. The improvement in survival rates for younger patients diagnosed more recently reflects advancements in treatment and care.This research provides valuable insights into the factors affecting breast cancer survival rates, underscoring the role of socioeconomic status, age, and comorbidities while also highlighting the progress in breast cancer treatment over recent years.